Building an environmentally accountable medical curriculum through international collaboration. (3rd October 2017) - Walpole, Sarah Catherine; Vyas, Aditya; Maxwell, Janie; Canny, Ben J.; Woollard, Robert; Wellbery, Caroline; Leedham-Green, Kathleen E.; Musaeus, Peter; Tufail-Hanif, Uzma; Pavão Patrício, Karina; Rother, Hanna-Andrea
Abstract: Background: Global environmental change is associated with significant health threats. The medical profession can address this challenge through advocacy, health system adaptation and workforce preparedness. Stewardship of health systems with attention to their environmental impacts can contribute to mitigation of and adaptation to negative health impacts of environmental change. Medical schools have an integral role in training doctors who understand the interdependence of ecosystems and human health. Yet integrating environmental perspectives into busy medical curricula is not a simple task. Content: At the 2016 Association for Medical Education in Europe conference, medical educators, students and clinicians from six continents discussed these challenges in a participatory workshop. Here we reflect on emerging themes from the workshop and how to plan for curricular change. Firstly, we outline recent developments in environmental health and associated medical education. Secondly, we reflect on our process and outcomes during this innovative approach to international collaboration. Thirdly, we present learning objectives which cover core content for environmentally accountable medical curricula, developed through a reflective process of international collaboration integrating current literature and the workshop outcomes. Conclusions: International collaboration can bring together diverse perspectives and provide critical insights for the inclusion of environmental health into basic education for medical practitioners.